PERANCANGAN SISTEM INFORMASI ABSENSI FINGERPRINT BERBASIS WEBSITE PT. MEDIA ANDALAN NUSA (ANDALWORKS) - Edo Arribe; Muhammad Ryandi (JURNAL ILMIAH INFORMATIKA, 2023)
An attendance information system is crucial for managing employee presence within a company or organization. This research aims to develop and design a web-based fingerprint attendance system that provides an efficient and accurate solution for recording and monitoring employee attendance. The research methodology involves collecting data through methods such as observation, interviews, and literature review. The system development method employed in this study is the waterfall method. This web-based fingerprint attendance information system allows easy access from various internet-connected devices. Employee attendance data will be automatically recorded and stored in a centralized database. Furthermore, the system includes reporting features that enable managers or administrators to monitor and analyze employee attendance data. In conclusion, this web-based fingerprint attendance system offers an efficient and integrated solution for monitoring employee attendance data in a company or organization. The aim is to improve the efficiency and effectiveness of managing employee attendance.